Effect of increased CO2 and iron levels on the marine plankton food web during a mesocosm experiment - Segovia, MR (My University, 2015)
A mesocosm experiment was carried out in the Raunefjord (Norway) during 25 days, to investigate the interactive effects of increased CO2 and iron availability on the plankton community. The seawater carbonate system in the mesocosms was manipulated to achieve two different CO2 levels, corresponding to the present (390 ppmv, LC) and to levels predicted for year 2100 (900 ppmv, HC), in combination with ambient and increased dissolved Fe (dFe) concentrations in a full factorial design. We observed a shift in the plankton community structure, initially dominated by picoeukaryotes and small nanoeukaryotes, changing to an Emiliania huxleyi dominated bloom. E. huxleyi and Synechococcus were the most sensitive organisms to changes in CO2 and Fe levels, being negatively affected by increased CO2 and favoured by high dFe levels. Picoeukaryotes, large nanoplankton, viruses and ciliates abundances were not affected by changes in CO2 or dFe levels. Bacterial abundance showed a significant positive response to high CO2 but it was unaffected by dFe. Total mesozooplankton abundances did not change significantly. The relevance of these results within the global change scenario will be discussed.
Keywords: Fitoplancton marino; Marine biology; Mesocosm; Iron; Co2; Phytoplankton